Alterations in white matter integrity in first-episode, treatment-naive patients with somatization disorder. (10th July 2015) - Zhang, Jian; Jiang, Muliang; Yao, Dapeng; Dai, Yi; Long, Liling; Yu, Miaoyu; Liu, Jianrong; Zhang, Zhikun; Xiao, Changqing; Guo, Wenbin
Highlights: Patients with somatization disorder had reduced fractional anisotropy(FA). Patients with somatization disorder showed increased mean diffusivity(MD). Lower FA is correlated with the score of somatization subscale SCL-90. Abstract: White matter (WM) abnormality in somatization disorder (SD) has not been reported yet. This study was designed to elucidate the alterations in WM integrity in SD. A total of 25 patients with SD and 28 healthy controls were enrolled in the study. WM integrity was analyzed using tract-based spatial statistics. No differences were found between the patients and the controls for fractional anisotropy (FA) values, mean diffusivity (MD), axial diffusivity, and radial diffusivity values at the corrected p < 0.05 level. Patients with SD had significantly decreased FA values in the cingulum and inferior fronto-occipital fasciculus, and significantly increased MD values in the anterior thalamic radiation and corticospinal tract compared with the controls at the uncorrected p < 0.005 level. Somatization severity was correlated with the FA values of the cingulum and inferior fronto-occipital fasciculus in the patients. The patients exhibit suggestive alterations in WM integrity in the cingulum, inferior fronto-occipital fasciculus, anterior thalamic radiation, and corticospinal tract.